PERKEMBANGAN AKUNTANSI SINGAPURA SERTA ANALISIS FINANCIAL SHENANIGANS PADA BLUMONT GROUP LTD - Natalis Christian; Friendty Friendty; Alfredo Crisitiano; Angellyn Lim; Uci Sufikat Maskat (Jurnal Ilmiah Akuntansi & Bisnis, 2021)
The development of accounting is related to manipulating financial performance. Accounting includes organizations, certification profession, and financial reporting standards in that country. Financial shenanigans is an action planned to manipulate the financial performance of a company which consists of seven categories. This article describes a comparison between the development of accounting for Indonesia and Singapore, and an analysis of seven financial shenanigans in manipulating financial performance Blumont Group Ltd, a business service company located in Singapore, where was involved in a case of very high new share price manipulation with two listed Singapore companies, Asiasons Capital Ltd and LionGold Corp Ltd in 2013. The research method explains based on facts in Singapore and the financial statements 2016-2020 of Blumont Group Ltd. The results explain that there isn’t evidence that the Blumont Group Ltd company does shenanigans one, two, four, five, six and seven, but was found to practice shenanigans three. Keyword: The development of accounting, Financial Shenanigan, Singapore, Indonesia, Manipulation.